2022
DOI: 10.1039/d1nj06198d
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the multifunctional activity of silver bionanocomposites in environmental remediation and inhibition of the growth of multidrug-resistant pathogens

Abstract: Synthesis of bio-based environmental remedial and antimicrobial products is an urgent need for the 21st century in the COVID-19 pandemic world. Keeping this in mind, cellulose-supported Ag bionanocomposites (AGC NCs)...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 142 publications
(244 reference statements)
0
3
0
Order By: Relevance
“…Along with the bactericidal effect of Ag, the extensive surface area of Ag NPs makes the NPs profitable antimicrobial agents 19 . Several Ag NPs were used against some gram-positive and gram-negative bacteria, they were jasmine flower extract synthesized Ag NPs against Staphylococcus aureus and Escherichia coli 7 , Alpinia nigra fruits mediated Ag NPs against Klebsiella pneumoniae, Staphylococcus aureus and, Candida albicans 8 , onion peels mediated Ag NPs mediated Salmonella typhimurium and Staphylococcus aureus 3 , etc... In our study, Livistona jekinsiana and Lasia spinosa were applied in the synthesis of Ag NPs for the first time.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Along with the bactericidal effect of Ag, the extensive surface area of Ag NPs makes the NPs profitable antimicrobial agents 19 . Several Ag NPs were used against some gram-positive and gram-negative bacteria, they were jasmine flower extract synthesized Ag NPs against Staphylococcus aureus and Escherichia coli 7 , Alpinia nigra fruits mediated Ag NPs against Klebsiella pneumoniae, Staphylococcus aureus and, Candida albicans 8 , onion peels mediated Ag NPs mediated Salmonella typhimurium and Staphylococcus aureus 3 , etc... In our study, Livistona jekinsiana and Lasia spinosa were applied in the synthesis of Ag NPs for the first time.…”
Section: Introductionmentioning
confidence: 90%
“…Many plants are used in the synthesis of Ag NPs. Alpinia nigra fruits mediated Ag NPs 6 , jasmine flower extract synthesized Ag NPs 7 , Artocarpus heterophyllus and Azadirachta indica mediated Ag NPs 1 , Citrus medica, Tagetes lemmonii, and Tarenna asiatica assisted Ag NPs 8 , onion peels mediated Ag NPs 9, etc. Polyphenolic compounds present in the plant extracts reduced Ag+ ions to Ag(0) NPs and stabilized them by capping around the NPs 2 .…”
Section: Introductionmentioning
confidence: 99%
“…In addition to conductivity, these polymers display also antibacterial activity [6][7][8][9][10]. Five organic dyes differing in molecular structure have been selected for the present study (Figure 2) for their antibacterial effect reported in the literature: crystal violet (triphenylmethane dye) [14][15][16][17], neutral red (phenazine dye) [18,19], methyl orange (azo dye) [20], acriflavine (acridine dye) [21][22][23], and methylene blue (thiazine dye) [18,22,24].…”
Section: Introductionmentioning
confidence: 99%